PENGARUH PARAMETER PENGGURDIAN TERHADAP AKURASI LUBANG KOMPOSIT GONI-POLIESTER DENGAN TWIST DRILL - Radiansyah Giga Suhartono; Anggit Murdani (Journal of Applied Mechanical Engineering and Renewable Energy, 2022)
Composite is a combination of materials consisting of 2 or more materials lead to the composite material has different mechanical properties and characteristics as desired. Composite materials are divided into two types, synthetic fibers and natural fibers. Most of the natural fiber types use jute fiber, as it is a candidate as a reinforce material to produce lightweight, strong and environmentally friendly composite materials as mixing polyester composites. Although composites can be made according to the desired shape, the final work, such as the machining process, is also needed for making several shapes such as making holes with the drill process. Furthermore, twist drilling, can induce damage due to the imperfections of the holes that are produced, resulting asymmetrical holes. This allows complicate assembly and reduce its strength. The parameters use are spindle speed 100 rpm, 700 rpm and 1400 rpm and feeding 0,1 mm/rev, 0,2 mm/rev, 0,3 mm/rev, 0,5 mm/rev and 0,7 mm/rev. The results obtained that using 100 rpm and feeding 0.5 to 0.7 can make imprecise and resulted delamination of the hole. Increased spindle speed such as 700 and 1400 rpm and higher feed rate, resulted increase the accuracy of the hole